The effect of complex training on physical performance in rugby league players - Scott, D. J.; Ditroilo, M.; Orange, S. T.; Marshall, P. (International Journal of Sports Physiology and Performance, 2023)
Purpose: To compare the effects of variable-resistance complex training (VRCT) versus traditional complex training (TCT) on strength, power, speed, and leg stiffness (Kleg) in rugby league players during a 6-week mesocycle.